Preclinical evaluation of a novel antibiotic-eluting BioEnvelope for CIED infection prevention - Garrigos, Zerelda Esquer; Catanzaro, John N.; Deegan, Daniel; Zhang, Ji; Sohail, M. Rizwan (Frontiers in Drug Delivery, 2024)
The risk of infection remains a significant concern with cardiovascular implantable electronic devices, necessitating the development of new strategies. This study explores the efficacy of a novel antibiotic-eluting biologic envelope designed to mitigate infection risk through localized antibiotic delivery while preserving the regenerative properties of biological matrix. Antibiotics, rifampin and minocycline, are released through polymer discs, ensuring extended drug release. Utilizing an established model of infection in a New Zealand White rabbit, the study assessed performance against gram-positive bacterial strains, including common pathogens such as S. aureus and S. epidermidis associated with CIED infections, and gram-negative bacterial strains. Results demonstrated strong antibacterial activity, achieving complete eradication of bacterial colonies and greater than 6-log reductions in colonization for all strains. Pharmacokinetic analysis revealed sustained local antibiotic concentrations at the implantation site for up to 14 days, with minimal systemic exposure, demonstrating the advantages of localized drug delivery. Health outcomes in the antibiotic bioenvelope group were significantly improved, with no signs of infection or abnormal body temperatures, in contrast to the control group. Macroscopic examinations post-necropsy confirmed the absence of infection at the implantation sites of animals receiving the antibiotic bioenvelope. The combination of localized antibiotic delivery in a regenerative matrix positions the antibiotic bioenvelope as a promising solution for preventing CIED-related infections.